Prognostic nutritional index as a biomarker for identifying coronary artery lesions in Kawasaki disease - Chao Zhang; Guoshun Mao; Guosheng Hu (Jornal de Pediatria)
Objective: To evaluate the Prognostic Nutritional Index as a biomarker for identifying coronary artery lesions in Kawasaki disease. Methods: The clinicopathological and laboratory characteristics of 241 patients with Kawasaki disease were collected from patients who were hospitalized in Fuyang People's Hospital from January 2018 to December 2024. Logistic regression analysis was conducted to evaluate the relationship between Prognostic Nutritional Index and coronary artery lesions. The critical levels of hematological parameters were determined by receiver operating characteristic analysis. Results: The incidence of coronary artery lesions was 10.3 %. The optimal cut-off point for the Prognostic Nutritional Index was defined as 46.575. Prognostic Nutritional Index was negatively correlated with coronary artery diameter (r = −0.260, p < 0.001). Patients with low Prognostic Nutritional Index levels (Prognostic Nutritional Index < 46.575) were 4.25 times more likely to have coronary artery lesions compared to those with high Prognostic Nutritional Index levels (Prognostic Nutritional Index ≥ 46.575) (OR = 4.25, 95 % CI: 1.688 - 10.697, p < 0.001). The area under the receiver operating characteristic curve for Prognostic Nutritional Index in predicting coronary artery lesions was 0.702 (95 % CI: 0.584 - 0.821, p = 0.001), indicating moderate diagnostic efficacy. Conclusion: Prognostic Nutritional Index may be a biomarker for children with Kawasaki disease complicated with coronary artery lesions, and it may help identify high-risk patients of coronary artery lesions among children with Kawasaki disease.